Evaluation of PEGylated Exendin‐4 Released from Poly (Lactic‐co‐Glycolic Acid) Microspheres for Antidiabetic Therapy. Issue 1 (18th November 2014) - Lim, Sung Mook; Eom, Ha Na; Jiang, Hai Hua; Sohn, Minji; Lee, Kang Choon
<x xml:space="preserve">Abstract</x> Peptide‐based therapies have the potential to induce antibody formation if the molecules differ from a native human peptide. Several reports have disclosed the occurrence of antibody generation in a patient treated with exenatide. The immune response can be problematic from a clinical stand point, particularly if the antibodies neutralize the efficacy of the biotherapeutic agent or cause a general immune reaction. To overcome this limit, PEGylated exendin‐4 analogs were designed and examined for metabolic stability and biological activity. To develop an extended release delivery system for exendin‐4 for the safe and effective delivery of bioactive exendin‐4 without peptide acylation and immunogenicity, PEGylated exendin‐4 was encapsulated into poly (lactic‐co‐glycolic acid) (PLGA) microspheres by w/o/w double emulsion solvent evaporation method. Peptide‐loaded microspheres were characterized in terms of morphology, particle diameter, and peptide encapsulation efficiency. Then, the release profile of the peptide from PLGA microspheres and the acylated products from PLGA polymer degradation was determined. The results obtained showed that the stability of exendin‐4 was greatly improved by PEGylation. Moreover, eliminated acylation during PLGA polymer degradation in vitro and reduced immunogenicity in vivo were observed. The findings demonstrate that PEGylated exendin‐4‐loaded microspheres may be a safe and biocompatible system for clinical development. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:72–80, 2015